Alopecia Management Potential of Rosemary-Based Nanoemulgel Loaded with Metformin: Approach Combining Active Essential Oil and Repurposed Drug - Abla KK; Alamoudi MK; Soliman GA; Abdel-Kader MS; Aldawsari MF; Mehanna MM (International Journal of Nanomedicine)
Kawthar K Abla,1 Mariam K Alamoudi,2 Gamal A Soliman,2,3 Maged S Abdel-Kader,4,5 Mohammed F Aldawsari,6 Mohammed M Mehanna7,8 1Department of Pharmaceutical Science, Faculty of Pharmacy, Beirut Arab University, Beirut, Lebanon; 2Department of Pharmacology, College of Pharmacy, Prince Sattam Bin Abdulaziz University, Al-Kharj, Saudi Arabia; 3Department of Pharmacology, College of Veterinary Medicine, Cairo University, Giza, Egypt; 4Department of Pharmacognosy, College of Pharmacy, Prince Sattam Bin Abdulaziz University, Al-Kharj, Saudi Arabia; 5Department of Pharmacognosy, College of Pharmacy, Alexandria University, Alexandria, Egypt; 6Department Pharmaceutics, College of Pharmacy, Prince Sattam Bin Abdulaziz University, Al-Kharj, Saudi Arabia; 7Department of Pharmaceutical Sciences, School of Pharmacy, Lebanese American University, Byblos, Lebanon; 8Department of Industrial Pharmacy, Faculty of Pharmacy, Alexandria University, Alexandria, EgyptCorrespondence: Mohammed M Mehanna, Department of Industrial Pharmacy, Alexandria University, Alexandria, Egypt, Email mohamed.mehanna@alexu.edu.egIntroduction: Androgenetic alopecia (AGA) is a multifactorial and age-related dermatological disease that affects both males and females, usually at older ages. Traditional hair repair drugs exemplified by minoxidil have limitations such as skin irritation and hypertrichosis. Thus, attention has been shifted to the use of repurposing drugs. Metformin is an anti-diabetic drug, that can promote hair follicle regeneration via upregulation of the hair-inductive capability. Hence, the current study aims to fabricate a safe and effective nanoemulsion to improve metformin efficacy in targeting AGA.Methods: Rosemary oil was selected as the oily phase due to its ability to increase blood flow and hair growth. Rosemary-based nanoemulsions were statistically optimized by Box-Behnken experimental design, loaded with metformin, and incorporated into a hydrogel to form a nanoemulgel. Metformin-loaded nanoemulsions were assessed for their diametric size, uniformity, zeta potential, and metformin characteristics within the formulated nanosystem. The nanoemulgel was then evaluated in terms of its pH, percentage drug content, and in-vitro release performance. In-vivo study assessed the nanoemulgel’s ability to augment hair growth in rats.Results: The experimental design displayed that using 50%w/w, 20%w/w, and 10%w/w of Cremophor®, Labrafil®, and deionized water, respectively, resulted in nanoemulsion formulation with the smallest globule size (125.01 ± 0.534 nm), unimodal size distribution (PDI=0.103), negative surface charge (− 19.9 ± 2.01 mV) with a spherical morphological structure. Rosemary-based nanoemulgel displayed acceptable physicochemical characterizations namely; a neutral pH value of 6.7± 0.15, high drug content (92.9± 2.3%), and controlled metformin in-vitro release. Besides, the formulated nanoemulgel significantly increased the number of hair follicles in the animal model compared with other controls and tested groups.Conclusion: The designed nanoemulgel is a promising approach for treating androgenic alopecia. Keywords: androgenic alopecia, emulgel, metformin, nanoemulsion, rosemary oil, quality by design